Prevalence of concomitant hypo-hyperdontia in a group of Turkish orthodontic patients - KARGÜL, BETÜL (SPRINGER, 2016)
Aim Was to investigate hypodontia and supernumerary teeth, in the same individual, which is termed 'concomitant hypo-hyperodontia' (CHH) and the frequency of CHH in a large sample of non-syndromic orthodontic patients. Methods In this retrospective study, the records were reviewed of 1236 Turkish orthodontic patients treated between 1994 and 2003 at Marmara University, Paediatric Clinics. Data were collected and analysed for differences in the distribution of hypodontia and supernumerary teeth, sex, and malocclusion type. Results A total of 1236 orthodontic patients were included in this study. The mean age of children was 17.05 years (SD = 2.5). The prevalence of hypodontia was 7 % (82) and was more frequently found in girls. Concomitant hypo-hyperodontia was found in 9 children, involving 8 boys and 1 girl. The frequency of mesiodens in hypodontia patients with Class I, II, and Class III malocclusions was 3 (3 boys), 5 (5 boys) and 1 (1 girl), respectively. CHH prevalence was found 0.7 % (9 patients). The gender ratio was 0.2:1.1 for CHH. Conclusions Supernumerary teeth may lead to some clinical problems including malocclusions, aesthetic and functional complaints, and also psychological problems. Early diagnosis of the condition and multidisciplinary approach for management of such cases is recommended.
Keywords: Concomitant hypo-hyperdontia; Non-syndromic hypodontia; Mesiodens; Turkish children; DENTAL ANOMALIES; PERMANENT TEETH; HYPODONTIA; POPULATION